DOTA-tris(OPp ester) as a bifunctional prochelator for the preparation of DOTA-peptide conjugates - Jamous, Mazen; Haberkorn, Uwe; Mier, Walter (Tetrahedron letters, 2012)
Peptides containing the chelator DOTA have gained importance for molecular imaging and therapy with radionuclides. However, all synthons described for the convergent solid phase synthesis of DOTA-peptide conjugates show windows of stability that are too narrow to allow a clean and convergent deprotection process. The synthesis of the new prochelator DOTA-tris(OPp ester) starting from cyclen is reported. Using this prochelator for the synthesis of several DOTA peptide conjugates revealed that its cleavage—in contrast to the cleavage of DOTA-tris(tBu ester) conjugates—does not require an extended deprotection time, and therefore results in clean and homogenous products.